Post-recession business growth: impact on ROE in the long and short term; RETOS. Revista de Ciencias de la Administración y Economía; Vol. 14, No. 28 - Spitsin V. V. Vladislav Vladimirovich; Ryzhkova M. V. Marina Vyacheslavovna; Spitsina (Spitsyna) L. Yu. Lubov Yurievna; Leonova V. A. Victoria Aleksandrovna (2024, 2024)
Title screen